The role of interreligious dialogues on religious tolerance - Mahmood Vaezi (HTS Teologiese Studies/Theological Studies, 2018)
The application of the word ‘dialogue’ has a life as long as history and the old texts of religions are full of dialogues prevailing among different religious people. Reviewing and analysing the background and history of religious dialogue in the world, more than anything else, we understand the principle of necessity and position of dialogue as a common and public principle among religions, which in a broader view has been acceptable to most, if not all, religious people. This issue indicates that a spiritual and inherent sense is within the substantial core of all humans towards dialogue, which as a natural and inherent feature has been prevailing from the beginning of creation up to the present, and it will continue so. Firstly, employing the dialogue or saying and listening either to the inner self or the other people, when it is being formed with a commitment to human principles, will make human overpass a self-oriented attitude and recognition other persons. Secondly, it makes him/her listen and tolerate others’ views. Thirdly, it makes him/her be committed towards the principle of tolerance and recognise of the other(s) as well. On this basis, the continuity of the principle of dialogue and emphasis on this innate tradition will cause the spread of the culture of tolerance, peace and tranquillity. Furthermore, distancing from dialogue will lay down grounds for a self-oriented attitude, prejudice, pride, omission of others and violence in human society. On this case, while giving originality to dialogue, Islam clearly and firmly puts dialogue forth as a basic principle in human relations and a base to achieve the common ideals of human communities, which are discussed in detail in this article.